2018
DOI: 10.3389/fphar.2018.00436
|View full text |Cite
|
Sign up to set email alerts
|

Mequindox-Induced Kidney Toxicity Is Associated With Oxidative Stress and Apoptosis in the Mouse

Abstract: Mequindox (MEQ), belonging to quinoxaline-di-N-oxides (QdNOs), is a synthetic antimicrobial agent widely used in China. Previous studies found that the kidney was one of the main toxic target organs of the QdNOs. However, the mechanisms underlying the kidney toxicity caused by QdNOs in vivo still remains unclear. The present study aimed to explore the molecular mechanism of kidney toxicity in mice after chronic exposure to MEQ. MEQ led to the oxidative stress, apoptosis, and mitochondrial damage in the kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Chronic studies of MEQ on rats induced adrenal toxicity ( Huang et al, 2009 ), invoked oxidative stress in liver and kidney ( Huang et al, 2010b ), and caused hepatic histological changes ( Ihsan et al, 2010 ). Recent studies revealed that toxicity of liver, kidney, and testis in mice was induced by MEQ at a dose level of 25, 55, and 110 mg/kg diet ( Liu et al, 2017b , c , d , 2018a ). In genotoxicity tests, MEQ exhibited a strong genotoxic potential to bacteria, mammalian cells in vitro and in vivo and its mutagenicity is slightly higher than CBX ( Ihsan et al, 2013a ; Liu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic studies of MEQ on rats induced adrenal toxicity ( Huang et al, 2009 ), invoked oxidative stress in liver and kidney ( Huang et al, 2010b ), and caused hepatic histological changes ( Ihsan et al, 2010 ). Recent studies revealed that toxicity of liver, kidney, and testis in mice was induced by MEQ at a dose level of 25, 55, and 110 mg/kg diet ( Liu et al, 2017b , c , d , 2018a ). In genotoxicity tests, MEQ exhibited a strong genotoxic potential to bacteria, mammalian cells in vitro and in vivo and its mutagenicity is slightly higher than CBX ( Ihsan et al, 2013a ; Liu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of HgCl 2 and treatment agents on the expressions of renal VCAM-1, cystatin C and podocin were determined by RT-PCR as previously described [ 41 ]. Amplification of cDNA was carried out using SYBR green master mix (Thermo Fisher Scientific, Waltham, MA, USA) in the presence of target primers ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The signal amplification was then detected and quantified using ABI 7500 real-time PCR System (Applied Biosystems, USA). The obtained data were analyzed using the 2 −ΔΔCt method [ 41 ] and normalized to β-actin.…”
Section: Methodsmentioning
confidence: 99%
“…Quinoxaline-1,4-dioxides (QdNOs), a group of synthetic antibacterial agents, were used in animal husbandry because of their strong antimicrobial activity. , It is reported that QdNOs ameliorate the intestinal microflora and promote the utilization and synthesis of protein in vivo . , Quinocetone (QCT), olaquindox (OLA), carbadox (CBX), and mequindox (MEQ) belong to QdNOs. However, it was reported that CBX, OLA, and MEQ were genotoxic carcinogens, , and because of these adverse effects, CBX and OLA were prohibited in food-producing animals. Cyadox, is a relatively new synthetic quinoxaline derivative with a broad antimicrobial spectrum. Cyadox has strong growth-promoting activity to poultry, fish, pigs, and goats with lower toxicity than other QdNOs. ,,, The previous studies demonstrated that cyadox had no genotoxic toxicity and carcinogenicity. ,, Therefore, cyadox has the potential to be widely used as an antibacterial agent.…”
Section: Introductionmentioning
confidence: 99%